PENGARUH PUPUK NPK TERHADAP PERTUMBUHAN DAN HASIL BERBAGAI VARIETAS PADI (Oryza sativa L.) DENGAN SISTEM SALIBU - Emmy Widyaningsih; Radian Radian; Basuni Basuni (Agros Journal of Agriculture Science, 2023)
The aim of the study was to determine the effect of NPK fertilizer and its varieties and their interactions on the growth and production of rice with the salibu system. The research was conducted in Kubu Raya Regency from June to September 2022. The research design used a factorial randomized block design. The first factor was the provision of NPK with 3 levels (NPK fertilizer dose of 200 kgha-1, 400 kg ha-1, 600 kg ha-1) and the second factor was the use of various types of varieties with 8 levels (Inpari 22, Inpari 24, Inpari 30, Inpari 32, Cilosari , Jeliteng, Baromah, Sulutan). The results showed that the NPK fertilization of various rice varieties in the crusading system was only able to affect plant height at the age of 5-6 WAC. NPK fertilization at a dose of 600 kg ha-1 can increase the growth and yield of rice in the crusader cultivation system in the variables of the number of productive tillers, the weight of harvested dry grain per clump, the weight of dry harvested and milled dry grain per plot and the potential for crop production per hectare. Not all rice varieties can produce good crosses. Varieties with high production potential per hectare are Inpari 32, Inpari 22, Sulutan, Baroma, Inpari 24, and Jeliteng varieties, respectively. Meanwhile, Inari 30 and Cilosari have milled dry unhusked rice and the lowest production potential, so it is not recommended to plant with the cruciferous system. The success of the cruciferous rice depends on the main crop, which is shown by the results of the main crops that align with the crusader rice yields. Keywords: NPK fertilizer, salibu, varietyINTISARITujuan penelitian untuk mengetahui pengaruh interaksi pupuk NPK dan varietas terhadap pertumbuhan dan produksi padi dengan sistem salibu. Penelitian dilakukan di Kabupaten Kubu Raya pada bulan Juni-September 2022. Rancangan penelitian menggunakan rancangan acak kelompok faktorial. Faktor pertama pemberian NPK dengan 3 taraf (dosis pupuk NPK 200 kg/ha, 400 kg/ha, 600 kg/ha) dan Faktor kedua penggunaan berbagai jenis varietas dengan 8 taraf (Inpari 22, Inpari 24, Inpari 30, Inpari 32, Cilosari, Jeliteng, Baromah, Sulutan). Hasil penelitian diperoleh bahwa pemupukan NPK berbagai varietas padi pada sistem budidaya salibu hanya mampu mempengaruhi tinggi tanaman pada umur 5-6 MSP. Pemupukan NPK dengan dosis 600 kg/ha dapat meningkatkan pertumbuhan dan hasil padi pada sistem budidaya salibu pada variabel jumlah anakan produktif, berat gabah kering panen per rumpun, berat gabah kering panen dan kering giling per petak serta potensi produksi tanaman per hektar. Tidak semua Varietas padi dapat menghasilakn salibu yang baik. Varietas yang mampu menghasilkan potensi produksi per hektar yang tinggi yaitu secara berturut-turut pada varietas Inpari 32, Inpari 22, Sulutan, Baroma, inpari 24, dan Jeliteng. Sedangkan Inpari 30 dan Cilosari memiliki Gabah Kering Giling dan  potensi produksi terendah sehingga tidak dianjurkan ditanam dengan sistem salibu. Keberhasilan padi salibu tergantung dari tanaman utamanya, yang ditunjukkan hasil tanaman utama yang sejalan dengan hasil padi salibu. Kata Kunci: pupuk NPK, salibu, varietas